Ragam Pola Tabuhan Instrumen Gambang Pada Musik Gambang Semarang - Abdul Rachman; Pramot Teangtrong; Phakamas Jirajaruphat; Udi Utomo; Syahrul Syah Sinaga; Ibnu Amar Muchsin; Sabrina Firda Sokhiba (Institut Seni Indonesia Denpasar, 2022)
Gambang Semarang is one of the traditional Indonesian music that grows and develops in the cityof Semarang, Central Java. Gambang Semarang music has an instrument made of wood which is the hallmark of Gambang Semarang music itself, namely Gambang. The Gambang instrument has a variety of distinctive accompaniment patterns that can give nuance to themusic of Gambang Semarang. The purpose of this study was to identify and describe the various patterns of accompaniment of the Gambang instrument in Semarang's Gambang music. The research method used is qualitative with an ethnomusicological approach. Data collection techniques were carried out by means of observation, interviews, document studies, and Focused Group Discussion. Data analysis was carried out with the stages of data reduction, data classification, and conclusions. The results showed that theaccompaniment pattern of the Gambang instrument in Gambang Semarang music consisted of an accompaniment pattern of gembyang nglagu oktaf, and a garap cengkok ajeg pattern. Each accompaniment pattern of the Gambang instrument involves a series of tones according to its seleh. Due to the influence of the melody of the main song, the accompaniment pattern of gembyang nglagu octaf and the accompaniment pattern of garap cengkok ajeg has six selehs, namely seleh do, seleh re, seleh mi, seleh sol, and seleh la.